Analisis Pelaksanaan Disiplin ASN Pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Kota Batu - Widyatmoko, Vicky Rahadyanto; Muchsin, Slamet; Ahmadi, Rulam; Afifuddin, Afifuddin (Universitas Nahdlatul Ulama Blitar, 2025)
This study aims to determine the implementation of ASN employee attendance discipline at the Human Resource Development and Civil Service Agency (BKPSDM) Batu City and the factors that influence it. This research is a qualitative study that uses interviews, documentation, and observation for data collection. The results showed the following. First, the leadership has implemented sanctions against violations of the attendance discipline. Second, the factors that support the implementation of ASN discipline in BKPSDM Batu City include: 1) the role of leadership role models and 2) the use of digital attendance. Leaders set a good example by being present on time and disciplined working hours, so that employees feel motivated. The use of digital absences also has a positive impact on discipline because the data cannot be manipulated. Third, the factors that become obstacles to improving discipline both time discipline and work discipline for ASN employees at BKPSDM Batu City include: 1) employees have not been able to manage the schedule of picking up and dropping off school children properly so that it interferes with working hours; 2) employees who violate consider the sanctions to be too light; 3) lack of effect from the sanctions received, for example a reduction in allowances or salaries; and 4) the level of tolerance for violations of attendance discipline is quite high. The leadership has set a good example in terms of attendance and accuracy of working hours.